1997
DOI: 10.1159/000461965
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Hepatitis C Virus Antibody with Specific Peptides in Seropositive Blood Donors and Comparison with Genotyping of Viral RNA

Abstract: Background and objectives: Serotyping of antibody to hepatitis C virus (anti- HCV) with specific peptides has been developed as an alternate method for typing HCV infections. The method does not require a prior amplification of viral RNA sequences from the sample. Identification of the viral genotype may be relevant for prognosis and clinical management. Materials and methods: We used a previously described HCV serotyping assay (RIBA™ HCV Serotype SIA kit, Chiron Corp.) to investigate the serotype in 191 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Some reports have suggested that including anti-E2 antibody testing into current EIA kits could improve their performance [14][15][16][17]. Our results shown here and elsewhere [19,20] demonstrated that E. coli-derived E2 fragments reacted specifically with infected patient sera in Western blot and elicited antibodies in rabbits against glycosylated E2 expressed in mammalian cells, indicating E2 proteins expressed in bacteria shared antigenic/immunogenic epitopes with mammalian E2 glycoproteins.…”
Section: Application Of E2n730(m) In the Detection Of Anti-e2 Antibodsupporting
confidence: 78%
See 1 more Smart Citation
“…Some reports have suggested that including anti-E2 antibody testing into current EIA kits could improve their performance [14][15][16][17]. Our results shown here and elsewhere [19,20] demonstrated that E. coli-derived E2 fragments reacted specifically with infected patient sera in Western blot and elicited antibodies in rabbits against glycosylated E2 expressed in mammalian cells, indicating E2 proteins expressed in bacteria shared antigenic/immunogenic epitopes with mammalian E2 glycoproteins.…”
Section: Application Of E2n730(m) In the Detection Of Anti-e2 Antibodsupporting
confidence: 78%
“…Therefore, E2 has become a major target in anti-HCV vaccine research. Humoral immune responses against E2 also have diagnostic significance, since there have been studies showing that testing for antibodies against E2 could improve the performance of current HCV EIA kits, which do not incorporate any forms of envelope proteins [14][15][16][17].…”
mentioning
confidence: 99%